Obstructive sleep apnoe and cardiovascular, heart failure and mortality outcomes with empagliflozin versus placebo in the EMPA-REG OUTCOME trial. (25th November 2020) - Yaggi, H.K; Eliasson, B; Kasai, T; Marx, N; Zinman, B; Inzucchi, S.E; Wanner, C; Zwiener, I; Wojeck, B; Neeland, I; Johansen, O
Abstract: Background/Introduction: Obstructive sleep apnoe (OSA) and type 2 diabetes (T2D) occurs more frequently in persons with obesity, and both OSA and T2D are associated with metabolic disturbances that increases the risk for cardiovascular disease (CVD). In EMPA-REG OUTCOME, a randomized placebo-controlled outcome trial involving 7020 patients with T2D and CVD, the sodium glucose co-transporter (SGLT)-2 inhibitor empagliflozin reduced HbA1c, systolic blood pressure, waist circumference, and weight, and also reduced the risk of 3-point major adverse CV events (3P- MACE) by 14%, CV death by 38% and hospitalization for heart failure (HHF) by 35%. Purpose: We investigated incidence rates of CV, HHF, and mortality outcomes in patients with or without OSA at baseline, and the treatment effect of empagliflozin, in EMPA-REG OUTCOME. Methods: The trial included patients from 42 countries with T2D (with HbA1c 7.0–9.0% for drug-naïve patients and 7.0–10.0% for those on stable glucose-lowering therapy), established CVD, and estimated glomerular filtration rate >30 mL/min/1.73 m 2 . Patients were randomised (1:1:1) to receive empagliflozin 10 mg, empagliflozin 25 mg, or placebo once daily in addition to standard of care. All CV outcomes were independently adjudicated and events were pooled for the 10 and 25mg doses. In this post-hoc analysis, OSA were assessed based on investigator reports using MedDRA 18.0 and incidence rates for outcomes were reported by adjusted event-rates per 100 patient-years. Analysis of effects on outcomes were performed using Cox regression models with multivariable adjustments. Results: Of 7020 patients with T2D and CVD, OSA was reported in 391 (5.6% [placebo 5.4%; pooled empagliflozin doses 5.7%]. Compared with patients without OSA at baseline, those with OSA were more frequent males (82.9% vs 70.8%), living in region North-America (63.2% vs 17.3%), and had more obesity (BMI ≥35 kg/m 2 : 55.2% vs 18.2%) and more coronary artery disease (88.0 vs 74.9%). Over a median 3.1 years, individuals with OSA at baseline relative to those without OSA in the placebo group, experienced 1.3–2.0 fold higher event rates for 3P-MACE (OSA vs no OSA: 6.49 vs 4.27/100-patient-year), CV death (2.57 vs 1.99), HHF (2.71 vs 1.38) and all-cause mortality (4.29 vs 2.78). Empagliflozin improved CV, HHF, and mortality outcomes regardless of presence of OSA at baseline (p-for interactions >0.05 [Figure 1]). Conclusions: In this post-hoc exploratory analysis, patients with OSA had higher frequency of events for 3P-MACE, HHF and mortality. The cardio-protective effects of empagliflozin was consistent in those with and without OSA at baseline. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boehringer Ingelheim and Eli Lilly Diabetes Alliance